Pengaruh Publicness Terhadap Hubungan Antara Partisipasi Pembuatan Anggaran Dengan Kinerja Manajerial - Alliyah, Siti (potensio, 2008)
This study aims to examine the relationship betweenparticipation in budget making and managing performance. Resultsobtained from these studies have been done was not consistent andthere was a contradiction between one researcher to another. Thisstudy provides empirical evidence about the effect of publicness onthe relation between participation in budget making and managingperformance in Universities and Hospitals both public and private.So that the budget can serve as a control, when compiling thebudget should be noted that the parties involved in preparing thebudget. One is that managers are directly responsible for managingperformance in a public or private organizations. The samplingmethod used was purposive sampling. In this study, sample criteriaare the managers who are at level two in their respective institutions.In the 70 private sector organizations and the public sector is 50.From the results of this study concluded that there are significantrelationships between participation publicness in budget making andmanaging performance.Key word: publicness, participation, and managerial performance